Diagnosis of paediatric tuberculosis by cartridge based nucleic acid amplification test and its effectiveness as compared to the other conventional diagnostic methods - Champatiray, Jyotiranjan; Patra, G. Dharmaraj (International Journal of Contemporary Pediatrics, 2019)
Background: Childhood TB constitutes 10-20% of all TB cases in high burden countries like India and accounting for 8-20% of TB related deaths. Diagnosis of TB in children is difficult. One test, CBNAAT which was recently endorsed by WHO has the potential to lead a revolution in diagnosis of active TB disease. Methods: A cross sectional study in SCB MCH and SVPPGIP, Cuttack in all the suspected TB patients admitted during the period from January 2016 to October 2017. Results: A total of 100 suspicious patients admitted to the Department of Pediatrics in SCB MCH and SVPPGIP during the study period. Of these 45 were diagnosed TB and rest others were diagnosed otherwise than TB. Diagnosis of TB was established on basis of Microscopy, CBNAAT, culture, biochemistry, cytology, clinical findings, neuroimaging, FNAC/biopsy, USG abdomen. Out of 45 TB patients 30 were CBNAAT positive taking the body fluid samples other than blood, urine and stool with a sensitivity of 66.7% and specificity of 100%. Out of 45 TB patients 14 were having ZN Smear positive taking the same fluid sample with a sensitivity of 31.1% and specificity of 100%. Whereas out of these 45 TB patients 32 were MGIT culture positive taking the same sample with a sensitivity of 71.1% and specificity of 100%. When diagnostic performances of CBNAAT and MGIT culture were compared, it was found to be statistically insignificant with a P value 0.54. Conclusions: The CBNAAT is able to confirm a diagnosis of TB with 66.7% sensitivity and 100% specificity within 2 hours. We can use CBNAAT as a diagnostic method as it provides rapid result and simultaneous better sensitive result, it can be helpful in starting ATT in sick patients and also in outdoor patients.